Molluscan distribution in and around Munroe Island, Kollam, Kerala - Puja Vijay; Nisha Keshav; Shynu; Sreela S R; Vishnu Mohan S; Aadithya S (International Journal of Marine Life, 2024)
The current investigation endeavors to comprehend the variation of Molluscan species, specifically gastropods, at Munroe Island in the Kollam district of Kerala. Munroe Island, is a traditional backwater village positioned at the meeting point of the Ashtamudi backwater and the Kallada River system. Comprising of eight small islands, it covers a combined area of 13.4 km2.The primary lithology of the island consists of sedimentary rocks on the mainland and low-lying areas of the delta region, located near the banks of the Kallada River and the confluence of Ashtamudi Lake. The region surrounding Munroe Island is part of the Asthamudi estuary, which is a significant geological feature of the South Indian peninsular shield. The estuary is primarily composed of crystalline rocks and tertiary sediments. The dominant lithology of the main island and its vicinity is made up of sedimentary rocks from the Warkalli and Quilon formations. Quaternary sediments of marine and fluvial origin can be found in the low-lying areas, particularly along the Kallada River and the western part near Asthamudi Lake, where numerous tidally active creeks are present. The coastal landscape and landforms exhibit a wide range of variations influenced by factors such as wave action, tides, currents, sedimentation, river stages, wind patterns, and the dynamic riverine environment. The newly discovered species on Munroe Island include Littoraria pallescens, Assiminea woodmasoniana, and Acteocina decorata the latter of which was initially documented in Ashtamudi Lake. The gastropods on Munroe Island have not been extensively studied, which has led to the initiation of this research aimed at examining the gastropod population in the area.
Keywords: Ashtamudi Lake; Gastropods; Kallada River; Munroe Island; mangroves